A new Fulvius species from Azores Islands (Heteroptera: Miridae: Cylapinae) - Frédéric, Chérot; Jordi, Ribes; Jacek, Gorczyca (Zootaxa, 2006)
The new species Fulvius borgesi is described from Azores Islands. The male and female genital structures are illustrated.